Decomposition of socioeconomic inequalities in child vaccination in Ethiopia: results from the 2011 and 2016 demographic and health surveys - Andrew Hayen; Firew Tekle Bobo (BMJ Open)
Objectives Monitoring and addressing unnecessary and avoidable differences in child vaccination is a critical global concern. This study aimed to assess socioeconomic inequalities in basic vaccination coverage among children aged 12–23 months in Ethiopia.Design, setting and participants Secondary analyses of cross-sectional data from the two most recent (2011 and 2016) Ethiopia Demographic and Health Surveys were performed. This analysis included 1930 mother–child pairs in 2011 and 2004 mother–child pairs in 2016.Outcome measures Completion of basic vaccinations was defined based on whether a child received a single dose of Bacille Calmette-Guerin (BCG), three doses of diphtheria, tetanus toxoids and pertussis (DTP), three doses of oral polio vaccine and one dose of measles vaccine.Methods The concentration Curve and Concentration Indices (CCIs) were used to estimate wealth related to inequalities. The concentration indices were also decomposed to examine the contributing factors to socioeconomic inequalities in childhood vaccination.Results From 2011 to 2016, the proportion of children who received basic vaccination increased from 24.6% (95% CI 21.4% to 28.0%) to 38.6% (95% CI 34.6% to 42.9%). While coverage of BCG, DTP and polio immunisation increased during the study period, the uptake of measles vaccine decreased. The positive concentration index shows that basic vaccination coverage was pro-rich (CCI=0.212 in 2011 and CCI=0.172 in 2016). The decomposition analysis shows that use of maternal health services such as family planning and antenatal care, socioeconomic status, exposure to media, urban–rural residence and maternal education explain inequalities in basic vaccination coverage in Ethiopia.Conclusions Childhood vaccination coverage was low in Ethiopia. Vaccination was less likely in poorer than in richer households. Addressing wealth inequalities, enhancing education and improving maternal health service coverage will reduce socioeconomic inequalities in basic vaccination uptake in Ethiopia.